The impact of natural removal on the release of nuclides into the containment after accident - Haiying Chen; Xinli Gao; Pingfei Du; Yuan Gao; Fudong Liu (International Journal of Advanced Nuclear Reactor Design and Technology)
The natural removal coefficient directly affects the amounts of radioactive iodine and aerosols released into the containment after the accident. The radioactivity calculation models in LOCA were established, and the impact of natural removal coefficients on the release of elemental iodine and aerosols into containment was quantitatively analyzed. The results showed that due to the comprehensive influence of factors such as core release type, release time, natural removal effect, nuclide decay, and containment leakage, the radioactivity of each nuclide in the containment reached its maximum value after 40 min of the accident, and then gradually decreased over time. During the effective natural removal time, there was a significant difference in the radioactivity of elemental iodine in the containment under different natural removal coefficients. Taking 131I as an example, the radioactivity ratio of elemental 131I in containment corresponding to the two natural removal coefficients decreased first and then increased over time. Finally, the radioactivity of elemental 131I under different natural removal coefficients was basically the same. The change of aerosol radioactivity in the containment was obviously affected by the value of natural removal coefficients. Under two different natural removal coefficients, the maximum radioactivity ratio of the aerosol nuclides in the containment was about 2.3.